2018
DOI: 10.1074/jbc.ra117.000866
|View full text |Cite
|
Sign up to set email alerts
|

LIM and cysteine-rich domains 1 is required for thrombin-induced smooth muscle cell proliferation and promotes atherogenesis

Abstract: Restenosis arises after vascular injury and is characterized by arterial wall thickening and decreased arterial lumen space. Vascular injury induces the production of thrombin, which in addition to its role in blood clotting, acts as a mitogenic and chemotactic factor. In exploring the molecular mechanisms underlying restenosis, here we identified LIM and cysteinerich domains 1 (LMCD1) as a gene highly responsive to thrombin in human aortic smooth muscle cells (HASMCs). Of note, LMCD1 depletion inhibited proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Previous studies have confirmed the function of LMCD1 in cardiac hypertrophy, thrombin formation, and hepatocellular carcinoma migration 29,55,56 . However, the role of LMCD1 in osteogenic differentiation of BMSCs and bone homeostasis has never been reported before.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have confirmed the function of LMCD1 in cardiac hypertrophy, thrombin formation, and hepatocellular carcinoma migration 29,55,56 . However, the role of LMCD1 in osteogenic differentiation of BMSCs and bone homeostasis has never been reported before.…”
Section: Discussionmentioning
confidence: 57%
“…In favor of this, it has been shown that LMCD1 inhibits DNA binding of transcriptional factor GATA6 and thus restricts its function during lung and heart development (Rath, Wang, Lu, & Morrisey, 2005). Likewise, by acting as a co‐activator with E2F transcription factor 1, LMCD1 stimulates human aortic smooth muscle cell (HASMC) proliferation and thereby promotes human atherogenesis (Janjanam et al, 2018). In this context, a precise balance between interactions with LMCD1 and NFAT1 is indispensable for the regulation of spatial and temporal activity of NFAT1 as well as other key transcriptional factors in phagocytic SCs.…”
Section: Discussionmentioning
confidence: 99%
“…Northern blot analysis shows that Lmcd1 is highly expressed in cardiac and skeletal muscles. Functionally, LMCD1 regulates cardiac hypertrophy (Bian et al, 2010) and thrombin‐induced smooth muscle cell proliferation (Janjanam et al, 2018) by interacting with different transcription factors. However, the physiological relevance of LMCD1 signaling beyond circulatory and musculoskeletal systems remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress directly targets the Lmcd1 transcription [15]. LMCD1 acts as a coactivator for E2F1 in the modulation of thrombin-induced CDC6 expression while promoting HASMC replication [16]. Par1, Gαq/11, PLCβ3, NFATc1, E2F1 and LMCD1 are involved in thrombin-induced IL-33 expression and migration [17].…”
Section: Lim and Cysteine-rich Domains-1mentioning
confidence: 99%